Management of Endocarditis Using Scintigraphy: An Overview - Wilhelm P. Mistiaen (Advanced Concepts in Medicine and Medical Research Vol. 12, 2024)
Introduction: Infective endocarditis (IE) is a very heterogeneous condition for several reasons. The diagnosis can be notoriously difficult. A delay in diagnosis can have severe consequences. Even proper application of the Duke criteria cannot solve all cases. For this reason, positron emission tomography / computer tomography (PET/CT) with 18F-fluorodesoxyglucose (18FDG) has been proposed in the 2015 guidelines of the European Society of Cardiology. What has been the effect of these guidelines thus far? Methods: A probe of the literature has been performed in PubMed, from 2016 on using the search terms “endocarditis AND PET”. PET with 18-fluoro-desoxyglucose (18-FDG) as marker for increased metabolism can serve such as in inflammation, infection and malignancies. Results: One hundred items were identified, of which 41 documents could be retained. However, only 16 were original series, mostly with low numbers. The other manuscripts were editorials, comments, reviews and “image vignettes”. PET/CT increased the sensitivity of the Duke criteria in cases of prosthetic valve endocarditis (PVE), but in a much lesser degree in native valve endocarditis (NVE). Patient preparation should be standardized in order to reduce the uptake of 18FDG by the myocardium. This includes low carbohydrate – high fat diet, fasting and unfractionated heparin administration. Furthermore, image acquisition and processing (quantification, correction for attenuation, taking into account implanted metallic materials) should also be standardized. Infection and inflammation of other causes such as postoperative healing and foreign body reaction should be discerned because of their different management and outcome. Scintigraphic techniques, based on radiolabeled WBC can serve as complement for distinction between sterile inflammation and infection. Effects of antibiotics (negative imaging results before cure) and inflammation (especially healing after operation and use of biological glue materials) should be taken into account. Radiolabeled white blood cell scintigraphy could be a valuable adjunct in these cases. The detection of extra- cardiac foci (especially tumors which can serve as port of entry and septic emboli) is an additional advantage. Conclusion: PET/CT seems a valuable tool to increase the accuracy in diagnosing IE, especially PVE. Early postoperative cases must be interpreted with caution. To confirm the value of PET/CT, the major centers should standardize their method. This allows comparison of results of larger patient groups, which could be collected in the International Collaboration of Endocarditis – Prospective Cohort Study. A standardized method for patient preparation, imaging acquisition and processing is needed. This can best be undertaken through the International Collaboration on Endocarditis– Prospective Control Study ICE-PCS. Nuclear cardiologists should also be included in “endocarditis teams.